Preparation, Characterization and Biological Study of New Derivatives of 1, 3, 4 - Thiadiazoleand Its Complexes with Some Transitional Element Ions. - Abd ALsada Alkafiji, Naeem; A.flifel, Ibrahim (University of Thi-Qar Journal of Science, 2019)
The current study involved preparation of ligand [2,5-bis-(2-(diphenyl methylene) hydrazineyl)-1,3,4-thiadiazole] (L1) from reacting between thiadiazole derivative [ (2,5-dihydrazineyl-1,3,4 -thiadiazol) and Benzphenone by the ratio (1:2) . Attended the transitional elements ions complexes [Cr+3, Fe+3, Co+3, Ni+2, Cu+2] with ligand (L1) Complexes were diagnosed using the precision analysis of elements (C.H.N), Infrared spectrum (FTIR), Spectrum of Nuclear Magnetic Resonance proton (1H-NMR), Mass spectroscopy, measurement magnetic sensitivity and measurement molar conductivity the results were practical exactly matching with the molecular and structural formulas of the proposed compound .Hyperchem was used to draw ligand (L1) and its complexes and to show the distribution of electronic density. Data obtained indicates that the stereochemistry figure of the complexes [Cr+3, Fe+3, Co+3] was octahedral , the proposed stereochemistry figure of the complexes [Ni+2, Cu+2] is square planer. A study was conducted testing the biological activity for the prepared ligand (L1) and its complexes against two types of bacteria staphylococcus aureus and Escherichia coli compared to the standard inhibitor (Cipro.), the results obtained confirmed that ligand(L1) and their complexes did not show any biological activity towards the bacteria aureus staphylococcus aureus, while the ligand(L1) and their complexes showed different activity twards the second type of bacteria Escherichia coli, some showed greater activity than the standard inhibitor and some showed less activity than the standard inhibitor